Preparation of Quartz Sand for Solar Photovoltaic Glass from Quartz Associated Kaolin by Size Fraction Distribution - Qianwei Zhang; Jianxin Wu; Qiang Fang; Xiaokang Liu; Runsheng Du; Fengjun Sun (Kuangchan zonghe liyong, 2023)
This is an essay in the field of ceramics and composites.To achieve carbon neutrality and peaking carbon dioxide emissions, the low-iron quartz sand(\begin{document}${{ ω }}_{{\text{Fe}}_{\text{2}}{\text{O}}_{\text{3}}}$\end{document}≤0.010%) supply for photovoltaic glass is tightening in China, so the preparation of low-iron quartz sand from quartz associated with kaolin gradually attracting widespread attention. However, quartz associated with kaolin can usually be enriched in the tailings of kaolin physical beneficiation. Taking quartz associated kaolin which is from tailings of kaolin physical beneficiation in Hepu, Guangxi as the object,the effect of purification by size fraction distribution on the preparation of low iron quartz sand from quartz-associated kaolin was studied in this essay. The experimental results showed that the index of SiO2, Al2O3 and Fe2O3 content in size of 2 mm or more was better than that of 0.71~2 mm and 0.125~0.71 mm respectively, but for all different size fraction products, ferric oxide content of quartz sand is not less than 0.016% by grinding, hydraulic classification, magnetic separation and flotation. The content of quartz sand obtained by sulfuric acid and oxalic acid was 0.0091%, and the content of quartz sand obtained by hydrofluoric acid and oxalic acid was 0.0054% respectively, both of which meets the ferric oxide content requirement of low iron quartz sand for solar photovoltaic glass and optical glass.